Histone Deacetylase Inhibitors Enhance Cell Killing and Block Interferon-Beta Synthesis Elicited by Infection with an Oncolytic Parainfluenza Virus - Fox, Candace R. (Viruses, 2019)
Previous results have shown that infection with the cytoplasmic-replicating parainfluenza virus 5 mutant P/V-CPI- sensitizes cells to DNA damaging agents, resulting in the enhanced killing of airway cancer cells. Here, we have tested the hypothesis that histone deacetylase (HDAC) inhibitors can also act with P/V-CPI- infection to enhance cancer cell killing. Using human small cell lung cancer and laryngeal cancer cell lines, 10 HDAC inhibitors were tested for their effect on viability of P/V-CPI- infected cells. HDAC inhibitors such as scriptaid enhanced caspase-3/7, -8 and -9 activity induced by P/V-CPI- and overall cell toxicity. Scriptaid-mediated enhanced killing was eliminated in lung cancer cells that were engineered to express a protein which sequesters double stranded RNA. Scriptaid also enhanced cancer cell killing by two other negative strand RNA viruses – the La Crosse virus and vesicular stomatitis virus. Scriptaid treatment enhanced the spread of the P/V-CPI- virus through a population of cancer cells, and suppressed interferon-beta induction through blocking phosphorylation and nuclear translocation of Interferon Regulatory Factor 3 (IRF-3). Taken together, these data support a role for combinations of a cytoplasmic-replicating RNA virus such as the P/V-CPI- mutant along with chemotherapeutic agents.